ANALISIS KOMPARATIF KINERJA PT. ENA DIVE CENTER DAN PT. NUSA DUA WISATA TIRTA: PERSPEKTIF BALANCED SCORECARD - Armi Widnyani, Ni Luh Putu; Alit Suardana, Ketut (E-Jurnal Akuntansi, 2015)
The research was conducted by taking secondary data and primary data. Secondary data is PT. Dive Center and PT. Nusa Dua Water Tourism for 3 years, from 2011-2013, and is the primary data is the result of a questionnaire to the respondents. Variables examined included the performance of a customer perspective, financial, internall business processes, and learning and growth. Assessment of financial performance assessed on the Return on Investment (ROI), customer perspective assessed on Customer Satisfaction Index (IKP), internal business process perspective assessed by SCE (Service Cycle Efficiency) is the coefficient of time in the process of assessment of customer service. Learning and growth perspective assessed from Employee Satisfaction Index (CCI). The results is that there are significant differences between PT. Ena Dive Center and PT. Nusa Dua Water Tourism in performance measurement using the balanced scorecard method.
Keywords: balanced scorecard, financial perfomance, customer perspective, internal bussines process, learning and growth perspective